The Influence of the Online Transportation Business on the Behavior of the Workforce in Indonesia (Case Study: Gojek Drivers in the Mertopolitan City of Medan) - Imam Sasri Try Nugraha (ProBisnis : Jurnal Manajemen, 2020)
The existence of online transportation Transportation Network Companies (TNC) in Medan City has caused controversy from various circles of society. The TNC is a competitor to conventional transportation and other public transportation means. On the one hand, the existence of online transportation can provide convenience for consumers and on the other hand is a threat to conventional types of transportation. Thus, the main objective of this research is to find out about the views of drivers why they choose to become drivers. The study was conducted using a survey method so that the main data used is primary data collected through interviews using a questionnaire to online transportation drivers. The existence of online transportation TNC is able to open up job opportunities in the transportation sector, but its impact on reducing unemployment remains to be studied further considering that most online transportation drivers already have jobs. The existence of online transportation in general is able to increase the income of online transportation drivers, the existence of online transportation has a positive influence on the income of TNC Grab and Gojek drivers.